Neuro Consilio: Stimulating visual, haptic, olfactory and auditory senses to promote passive recovery in acute brain injury and post operative neurological patients - Makula, Qaqamba (University of Pretoria, 2021)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2020.